THE INCIDENCE OF RADIATION PNEUMONITIS IN BREAST CANCER PATIENTS WHO RECEIVED RADIOTHERAPY USING 3-DIMENSIONAL TECHNIQUES - Salsabila Lutfiarahma; Yan Wisnu Prajoko; Farah Hendara Ningrum; Christina Hari Nawangsih Prihharsanti (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: According to the 2018 Global Cancer Observatory from the World Health Organization (WHO), breast cancer is the most common cancer in Indonesia. 3-dimensional conformal radiotherapy (3D-CRT) is one of the breast cancer treatment planning. Effect of radiation on the lungs can cause radiation pneumonitis. The incidence rate of pneumonitis in breast cancer patients who received radiotherapy using 3D-CRT techniques from several researchers is still varied and there is no accurate data yet at RSUP Dr. Kariadi.Objective: To determine the incidence of pneumonitis in breast cancer patients undergoing breast cancer 3D-CRT.Methods: The research design used in this study was cross sectional. The subject is chosen by consecutive sampling methods. The independent variables of this study was 3D breast cancer radiation therapy, while the dependent variable was radiation pneumonitis. This hypothesis test on this study is analyzed with chi-square test.Results: Forty one subjects were included in this study, two subjects were found with a picture of pneumonitis on chest radiographs. The incidence of radiation pneumonitis in breast cancer patients who received radiotherapy using 3-dimensional techniques was 4.9%. There is no significant relationship between breast cancer radiation therapy 3-dimensional techniques on the incidence of pneumonitis. And there was no significant difference in the proportion of pneumonitis in patients with breast cancer locations on the right and left sides.Conclusion: The incidence of radiation pneumonitis in breast cancer patients who received radiotherapy using a 3-dimensional technique is 4.9%. Keywords: 3 Dimensional Technique Radiotherapy, Breast Cancer, Radiation Pneumonitis